Pengaruh Locus of Control Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Nusa Toyotetsu Corp - Nurmala, Lala; Musadad, Anwar (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to test and analyze the effect of locus of control (X1) and work motivation (X2) on employee performance (Y). The sample in this study was 93 respondents from permanent employees at PT Nusa Toyotetsu Corp. Calculated using the Slovin formula with the Probability Sampling technique, the sample method was Stratified Random Sampling. The population in this study used employees of PT Nusa Toyotetsu Corp with a total of 1,330 permanent employees. This research was conducted using quantitative methods with descriptive and verification approaches. The statistic tools using SPSS version 23The results of the analysis conducted, the results show that locus of control has a significance value of 0.597> 0.05, which means that locus of control has no significant effect on employee performance. Work motivation has a significance value of 0.000 <0.05, which means that work motivation has a positive and significant effect on performance Simultaneously locus of control (X1) and work motivation (X2) together have a positive and significant influence on employee performance (Y) PT Nusa Toyotetsu Corp with a value of 46%, while the remaining 54% is another variable not examined in this study. 23The results of the analysis conducted, the results show that locus of control has a significance value of 0.597> 0.05, which means that locus of control has no significant effect on employee performance. Work motivation has a significance value of 0.000<0.05, which means that work motivation has a positive and significant effect on performance Simultaneously locus of control (X1) and work motivation (X2) together have a positive and significant influence on employee performance (Y) PT Nusa Toyotetsu Corp with a value of 46%, while the remaining 54% is another variable not examined in this study.